2020
DOI: 10.1021/acsnano.0c03362
|View full text |Cite
|
Sign up to set email alerts
|

Programming Biomimetically Confined Aptamers with DNA Frameworks

Abstract: Active sites of proteins are generally encapsulated within three-dimensional peptide scaffolds that provide the molecular-scale confinement microenvironment. Nevertheless, the ability to tune thermodynamic stability in biomimetic molecular confinement relies on the macromolecular crowding effect of lack of stoichiometry and reconfigurability. Here, we report a framework nucleic acid (FNA)-based strategy to increase thermodynamic stability of aptamers. We demonstrate that the molecular-scale confinement increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…It was previously reported that catalytic units can be tethered to “inner” or “outer” positions of DNA tetrahedra, and the resulting catalyst tethers reveal different catalytic activities (albeit quite small yet reproducible differences). 31 Accordingly, we designed DNA tetrahedra structures T A and T B that include hemin/G-quadruplex units in “inner” or “outer” positions and compared their activities to hemin/G-quadruplex tethered to a duplex DNA, Figure S17(A) . The different hemin/G-quadruplex structures were examined toward two different catalytic transformations: (i) the hemin/G-quadruplex catalyzed oxidation of Amplex Red by H 2 O 2 to form the fluorescent Resorufin, (ii) the hemin/G-quadruplex catalyzed oxidation of dopamine by H 2 O 2 to form aminochrome.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that catalytic units can be tethered to “inner” or “outer” positions of DNA tetrahedra, and the resulting catalyst tethers reveal different catalytic activities (albeit quite small yet reproducible differences). 31 Accordingly, we designed DNA tetrahedra structures T A and T B that include hemin/G-quadruplex units in “inner” or “outer” positions and compared their activities to hemin/G-quadruplex tethered to a duplex DNA, Figure S17(A) . The different hemin/G-quadruplex structures were examined toward two different catalytic transformations: (i) the hemin/G-quadruplex catalyzed oxidation of Amplex Red by H 2 O 2 to form the fluorescent Resorufin, (ii) the hemin/G-quadruplex catalyzed oxidation of dopamine by H 2 O 2 to form aminochrome.…”
Section: Resultsmentioning
confidence: 99%
“…The encapsulation of ribozymes inside vesicles is an important scenario in prebiotic evolution ( 10 12 , 66 , 67 ). Prior studies on isolated RNA sequences have pointed toward the possibility that encapsulation and related biophysical effects could increase ribozyme and aptamer activity ( 34 , 35 , 68 ), but the generality of these findings has been unclear. In addition, while compartmentalization is known to be important for the evolution of cooperative phenotypes ( 69 71 ), the evolutionary consequences of RNA encapsulation on noncooperative phenotypes have been largely unstudied, despite being the subject of speculations ( 13 , 72 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, confinement inside vesicles was shown to increase the binding affinity of the malachite green RNA aptamer ( 34 ). Interestingly, spatial confinement inside a tetrahedral DNA framework has also been shown to increase thermodynamic stability and binding affinity of aptamers by facilitating folding ( 35 ).…”
mentioning
confidence: 99%
“…The binding affinity of the aptamer is increased by ∼3 times after being modified on DNA framework. 73 In addition, DNA tetrahedra with tetravalent states can also be designed and covalently bonded to form various high-order nanostructures. 74,75…”
Section: Dna Tetrahedron Nanostructuresmentioning
confidence: 99%